Impact of coverage and quality of primary care on admissions for Primary Care-sensitive conditions in Sergipe of 2010 to 2019 (Research, Society and Development, 2022)
Hospitalizations for Sensitive Conditions to Primary Care (ICSAP) is an indicator used to assess the performance of the health system and Primary Care (AB). This study aimed to analyze the trends of these hospitalizations, in the State of Sergipe, from 2010 to 2019, in addition to describing the influence of coverage of AB and the participation of municipalities in the National Program for Improving Access and Quality of Primary Care (PMAQ) on the indicator. An ecological study of the ACSC time series was carried out by means of segmented linear regression analysis and correlation with the AB coverage trend and with the participation in the PMAQ. A stability was observed both in the ICSAP distribution rates and in the AB coverage during the analyzed decade, with no correlation between the two variables. Furthermore, a greater participation in the PMAQ and a good performance in the program proved to be capable of providing lower ICSAP rates and rate stagnation throughout the analyzed period. Thus, our study suggests that, as an indicator of the quality of AB, the ICSAP should be used concomitantly with an evaluation of other historical-structural aspects and that the PMAQ achieved its objective of increasing the access and quality of AB in the State of Sergipe.